MRI contrast agents and nephrogenic systemic fibrosis: why physicians should be concerned - Chhetri, PK (Journal of College of Medical Sciences-Nepal, 2010)
Magnetic Resonance Imaging (MRI) as a diagnostic tool is becoming increasingly available in Nepal and more and more patients undergo MRI examination today. It was also traditionally believed that MRI contrast agents are safer than Computed Tomography (CT) contrast agents and MRI was indicated where CT contrast agents were contraindicated. Of special note must be made of a rare and newly recognized disease that was described in patients with renal disease and given MRI contrast agents. It is thus of increasing importance for the radiologists and the physicians alike to be aware of this rare and newly recognized disease - nephrogenic systemic fibrosis. Key words: MRI contrast; computed tomography; nephrogenic systemic fibrosis. DOI: 10.3126/jcmsn.v6i1.3606 Journal of College of Medical Sciences-Nepal, 2010, Vol. 6, No. 1, 63-66